Brand advocates turning enthusiastic customers into a powerful marketing force - Fuggetta, Rob (Wiley, 2012)
"Brand advocates are your most loyal, passionate, and engaged customers. These enthusiastic customers don't just buy your products--they sell your products for you. Brand advocates tweet, blog, and Yelp about you; they praise you with five-star reviews on Amazon and TripAdvisor; they talk you up in social networks, online communities, and over coffee; and they defend you from detractors. According to social media firm, Vitrue, a Facebook fan may be worth $3.28. But, according to a study by customer satisfaction company, Satmetrix, a single brand advocate for an enterprise software company is worth $565,000 based on his referral value.This book is the go-to resource for teaching businesses how to make their customers be one of their most effective marketing components. The book explains how to find your brand advocates by determining levels of customer loyalty, and how to use their resources and power. Once you've found your advocates, the book explains how to get them to fill the gap from customer to advocate, from enjoying their experience to actively promoting their experience. The book gives you the secrets of turning advocates into marketers. You'll learn how to Discover who Brand Advocates are and what makes these influential customers tick Create and grow your Brand Army by continuously identifying advocates on Facebook, Yelp, and other online reviewer sites Energize and mobilize your Brand Army to spread positive Word of Mouth, create and maintain customers, and become your biggest supporters; Reward your advocates by giving them what they crave most Keep score. You'll learn how to measure results and ROI from online marketing programs featuring brand advocates "--